EFFECTS OF GAMMA-IRRADIATION ON THE DYEABILITY, WASH FASTNESS AND STAINING OF IRAQI COTTON FABBRICS - Mahmood, Amina (Iraqi Journal of Science, 2024)
The effects of "Co source of gamma - irradiation (0.1-1140) kGy on the dyeability, wash fastness and staining of Iraqi cotton fabrics were investigated for the first time, according to our knowledge, in an attempt to improve some characteristics of these fabrics that are used in the General Establishment for Cotton Industries. Color measurement was successfully applied as a tool in a study of the change versus dose, of dye uptake and wash fastness of cotton fabrics. At low doses it was found that the dye uptake initially decreased then increased with increasing dose, after that it increased steadily then rapidly with increasing dose. Staining and wash fastness of cotton fabrics dyed pre or post irradiation were also examined. A computer program was used to estimate changes in the color of the irradiated cotton fabrics as a result of dyeing, washing and staining. The results showed that a dose of 10 kGy favored optimum stain resistance and wash fastness properties for cotton fabrics dyed post irradiation. The overall behavior suggested that cotton fabrics were degraded at high doses (786-1140) kGy, while at low doses, the crosslinking between chains was the predominated process.